Empyema Necessitans in the Setting of Methicillin-Susceptible Staphylococcus aureus Causing Pneumonia and Bacteremia. (5th April 2018) - Bandaru, Sindhura; Manthri, Sukesh; Sundareshan, Vidya; Prakash, Vidhya
Abstract : Empyema necessitans (EN) is a rare phenomenon that refers to an insidious extension of the empyema through parietal pleura and subsequent dissection into subcutaneous tissue of the chest wall. A 29-year-old man presented to the hospital with fever and chills a few days after an inadvertent needle stick while injecting heroin. His left forearm was warm with an area of fluctuance. He underwent incision and drainage of the left forearm abscess with fluid submitted for Gram stain and culture. His condition rapidly deteriorated due to sepsis, and he required transfer to the intensive care unit. A new 4 × 3 cm area over the left pectoralis muscle had become increasingly indurated, fluctuant, and erythematous. CT of the chest demonstrated extensive cavitary lung lesions and a large loculated left-sided pleural effusion with extension through the chest wall. TEE revealed a 3 cm complex lesion on the superior septal leaflet of the tricuspid valve. The patient underwent incision and drainage of the pectoralis major EN with placement of a drain. Blood and sputum cultures grew methicillin-susceptible Staphylococcus aureus (MSSA) at which time antibiotic therapy was tailored to oxacillin. Our case highlights a rare occurrence of EN due to MSSA in a patient with intravenous drug use (IDU) and underscores the importance of prompt diagnosis and treatment.